Considerations Concerning the Evolution of the Local Development Strategy of Some Leader Territories in Arad County - Blaga, Radu Lucian (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Romanian National Rural Development Programme (NRDP 2007-2013) is the document, which applies EU Common Agricultural Policy in Romania as EU member state. LEADER, as part of EU Common Agricultural Policy was developed like territory planning policies focused on the rural area of intervention. It proved more effective and productive, being decided and implemented at local level by the local actors, using clear and transparent procedures for the evaluation of strategic objectives and plans, having the support of local governments and technical assistance necessary to transmit best practices. The European Agricultural Fund for Rural Development (EAFRD) finances investments in LEADER axis, using intervention areas (priority 1, priority 2 and priority 3) and related measures to NRDP. These measures can be found in a variable degree at the level of the Local Development Strategy (LDS) elaborated by The Local Action Groups (LAGs), LEADER territory concerned. Based on these issues, the paper seeks to present some practical considerations of the assessment of the LAG‟s activities in the implementation of strategy, scientifically linked to the portfolio analysis activities (intervention areas and measures) that compound the Local Development Strategy of some LEADER entities of the Arad County. The evaluation used outcome indicators for implementation of the Strategy.